Sentiment Analysis of Dune: Part Two Movie Reviews Using the Naive Bayes Method - Maheswari, Diyan Arum; Zy, Ahmad Turmudi; Afriantoro, Irfan (Information Technology and Science (ITScience), 2024)
Research on films is fascinating because of the profound changes that the development of information and communication technology has brought about in our interactions with and consumption of media content. This study performs sentiment analysis on